2013
DOI: 10.1080/10286020.2012.738673
|View full text |Cite
|
Sign up to set email alerts
|

Two new sesquiterpenoids from the rhizomes ofNardostachys jatamansi

Abstract: Phytochemical investigation of CHCl(3):MeOH (1:1) extract from the rhizomes of Nardostachys jatamansi led to the isolation of two new sesquiterpenoids (5 and 6), along with six known compounds (1-4, 7, and 8). The structures of two new compounds were established using IR, MS, 1D, and 2D NMR techniques. In addition, all the isolates were tested for their cytotoxicities against the A549 (lung cancer), DU-145 (prostate cancer), MCF-7 (breast cancer), and SK-N-SH (neuroblastoma).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The present study aimed to investigate the antioxidant and anticancer activity of the whole extract and subsequent fractions of N. jatamansi in breast cancer cells. Few research groups have evaluated the cytotoxic activity of N. jatamansi extract in various cancer cell lines [ 23 - 25 ], however, the mechanism of action of antiproliferative activity has not been investigated in breast cancer till date. These prompted us to investigate the anticancer potential of NJM extract and identify the most bioactive fraction with antiproliferative potential against ER-positive and ER-negative breast carcinoma cells and decipher the possible mechanisms of antiproliferative activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study aimed to investigate the antioxidant and anticancer activity of the whole extract and subsequent fractions of N. jatamansi in breast cancer cells. Few research groups have evaluated the cytotoxic activity of N. jatamansi extract in various cancer cell lines [ 23 - 25 ], however, the mechanism of action of antiproliferative activity has not been investigated in breast cancer till date. These prompted us to investigate the anticancer potential of NJM extract and identify the most bioactive fraction with antiproliferative potential against ER-positive and ER-negative breast carcinoma cells and decipher the possible mechanisms of antiproliferative activity.…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpenes are a promising class of natural compounds in cancer drug discovery with 3 compounds; artemisinin, thapsigargin and parthenolide currently being evaluated in clinical trials [ 58 ]. Other anticancer terpenoids from N. jatamansi include ursolic acid and 3-O-arabinosyl ursolic acid isolated from the cholorform:methanol fraction that showed cytotoxicity in lung (A-549), prostate (DU-145), breast cancer (MCF-7), and neuroblastoma (SK-N-SH) cells (IC 50 : 18–32 mM) [ 25 ]. Hence, the anticancer activity of the whole extract NJM and NJDE fraction against breast cancer cells could be attributed to the presence of a variety of compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetrazolium-based MTT assay was carried out as described in [29][30][31] with minor modifications. Briefly, 2 × 10 4 cells/well were seeded into 96-well plates.…”
Section: Mtt Assays For Measuring Cell Viabilitymentioning
confidence: 99%
“…N. jatamansi is belonging to Valerianaceae family; it is a small, hairy, perennial, erect, and rhizomatous herb. Phytochemical screening has revealed that it contained a large amount of bioactive compounds such as alkaloids, sesquiterpenes, lignans, coumarins, and steroids that are used for medicinal purposes [21,22]. This plant is appreciated for its antioxidant, antibacterial, stimulant, sedative, antifungal, antidiabetic, neuroprotective, hepatoprotective, anticancer, and cardioprotective properties [23][24][25].…”
Section: Introductionmentioning
confidence: 99%